2017
DOI: 10.1002/bies.201700106
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation in Embryo Development: Epigenetic Impact of ART (Assisted Reproductive Technologies)

Abstract: DNA methylation can be considered a component of epigenetic memory with a critical role during embryo development, and which undergoes dramatic reprogramming after fertilization. Though it has been a focus of research for many years, the reprogramming mechanism is still not fully understood. Recent results suggest that absence of maintenance at DNA replication is a major factor, and that there is an unexpected role for TET3-mediated oxidation of 5mC to 5hmC in guarding against de novo methylation. Base-resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 107 publications
2
56
0
3
Order By: Relevance
“…In a clinical context, this study has relevance in assisted reproductive techniques (ARTs) that are commonly used in human medicine and livestock breeding. Nowadays, children conceived using ART account for 2% of all births, which has brought the society a growing interest in their long-term health [ 12 ]. Moreover, in vitro production of bovine embryos is used worldwide for commercial purposes.…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical context, this study has relevance in assisted reproductive techniques (ARTs) that are commonly used in human medicine and livestock breeding. Nowadays, children conceived using ART account for 2% of all births, which has brought the society a growing interest in their long-term health [ 12 ]. Moreover, in vitro production of bovine embryos is used worldwide for commercial purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we have shown in a mouse model that fertilization through ICSI using DNA‐damaged spermatozoa increases the incidence of behavioral disorders, overweight, organomegaly, cancer and premature aging in the adult offspring (Fernandez‐Gonzalez et al, ). Considering the heterogeneity of epigenetic marks present also in the spermatozoa (Jenkins et al, ) and that not all male epigenetic marks are erased after fertilization (Canovas, Ross, Kelsey, & Coy, ), male epigenetic modifications could be another source of long‐term effects associated with ART. Some authors have suggested a relationship between imprinting disorders in the offspring conceived through ART and changes at imprinted loci in the sperm of men with oligozoospermia (Filipponi & Feil, ; Kobayashi et al, ; Kobayashi et al, ).…”
Section: Long‐term and Transgenerational Effects Of Artmentioning
confidence: 99%
“…The mechanism by which blastocyst transfer alters gene expression is not well understood, though epigenetic dysregulation has been implicated (Choux et al 2015, Canovas et al 2017. To examine the potential sensitivity of the DEGs to changes in DNA methylation, we first evaluated whether the top 50 downregulated genes (fold change >3.1) and top 50 upregulated genes (fold change >6.7) contained intragenic CpG islands or proximal promoter CpG islands (within 20 kb of the gene) ( Fig.…”
Section: Dysregulation Of Dna Methylation At Proximal Promoter Regionmentioning
confidence: 99%